Return Migration, Human Capital Accumulation and the Brain Drain - Christian Dustmann; Itzhak Fadlon; Yoram Weiss (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
In this paper we present a model that explains migrations as decisions that respond to where human capital can be acquired more efficiently, and where the return to human capital is highest. The basic framework is a dynamic Roy model in which a worker possesses two distinct skills that can be augmented by learning by doing. There are different implicit prices, in different countries and different rates of skill accumulation. Our analysis contributes to the literature on the selection of immigrants and return migrants by offering a richer framework that may help to accommodate selection of emigrants and return migrants that are not immediately compatible with the one-dimensional skill model. Our analysis also has implications for the debate on brain drain and brain gain. In the two skills model presented here, return migration can lead to a mitigation of the brain drain, or even the creation of a "brain gain", where those who return bring the home country augmented local skills.
Keywords: J3; J6; F2; 330; Return migration; human capital accumulation; comparative advantage; brain drain